1996
DOI: 10.1001/archinte.1996.00440100086010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adrenal and Extra-adrenal Conn Syndrome in Hypertensive Patients

Abstract: Although E-APT is rare, it should be considered in the interests of specific therapy for PA because aldosterone-secreting malignant ovarian tumors also have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…We did not include a study whose goal was to screen for PA among hypertensive patients with low PRA [23]. The seven eligible studies [1,2,10,[24][25][26][27] have been sorted by date of publication in Table 1. Using each authors' criteria, the prevalence of PA ranged from 4.6 to 14.4%, with an average of 6.6%.…”
Section: Primary Aldosteronism Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include a study whose goal was to screen for PA among hypertensive patients with low PRA [23]. The seven eligible studies [1,2,10,[24][25][26][27] have been sorted by date of publication in Table 1. Using each authors' criteria, the prevalence of PA ranged from 4.6 to 14.4%, with an average of 6.6%.…”
Section: Primary Aldosteronism Subtypesmentioning
confidence: 99%
“…To estimate the proportion of APA among patients with PA, we selected papers reporting diagnostic tests for PA and at least 50 patients with definite PA. To avoid an indication bias, we excluded surgical series in which all patients had been operated on. Among the nine eligible reports sorted by publication date in Table 2 [5,7,25,[28][29][30][31][32][33], the proportions of APA among patients with PA ranged from 24.2 to 77.4%, with an average of 56.6%. Finally, to estimate the frequency of hypertension cure or improvement following surgery, we analyzed series from single centres reporting postoperative BP follow-up in at least 50 patients with PA [34][35][36][37][38][39].…”
Section: Primary Aldosteronism Subtypesmentioning
confidence: 99%
“…Ectopic aldosterone‐secreting tumours (e.g. neoplasms in the ovary or kidney) are exceedingly rare 9 …”
Section: Introduction: ‘Painting Background’mentioning
confidence: 99%
“…1 But recent studies have suggested that primary hyperaldosteronism (PHA) may be present in at least 10% of patients. [2][3][4][5] These studies have used biochemical measures of autonomous aldosterone secretion, usually the ratio of plasma aldosterone to renin and the failure of aldosterone to suppress during treatment with salt supplementation. However, as often occurs when the arbiter for diagnosis changes -here, from anatomical to biochemical -the question arises whether the definition of the condition has also changed.…”
mentioning
confidence: 99%